Habitat fragmentation explains the occupancy probability of the largest herbivore in the Neotropical forests - Regolin, André Luis [UNESP]; Collevatti, Rosane Garcia [UNESP]; Bailey, Larissa Lynn; Boscolo, Danilo; Lautenschlager, Laís; Beca, Gabrielle; Dias, Viviane Brito [UNESP]; Galetti, Mauro [UNESP] (Elsevier, 2025)
Large mammals play an important role in ecosystem functioning, yet the loss of natural vegetation cover due to conversion to agriculture and other land uses has pushed wildlife into small and impoverished habitats. Thus, it is paramount to understand how landscape structure enables large mammals to thrive in tropical rainforests. We surveyed 42 forest landscapes in the Brazilian Atlantic forest for lowland tapir (Tapirus terrestris) using camera traps, analyzed landscape structure based on thematic maps, and assessed the matrix vegetation heterogeneity using satellite image texture. To evaluate the multiscale effects of the predictive variables on the species' occurrence probability, we used a single-season occupancy approach. Beyond advancing the understanding of the species' habitat requirements in human-modified landscapes, we used the species as a model to test theoretical predictions about the scale of effect (SoE), which have yet to be empirically evaluated. Habitat loss and fragmentation per se reduced the lowland tapir's occurrence, as did matrix vegetation heterogeneity. Different landscape metrics influenced species occupancy at distinct spatial scales, and the SoE of fragmentation metrics was not smaller than habitat amount. Habitat fragmentation at a wide scale was the main predictor of species occupancy probability. Our findings highlight the critical role of habitat spatial structure in shaping the distribution of the lowland tapir in human-modified landscapes. Beyond protecting large forest remnants, it is recommended to increase landscape connectivity at a broad scale through ecosystem restoration efforts to safeguard the species' persistence in the Brazilian Atlantic Forest.
A fragmentação do habitat explica a probabilidade de ocupação do maior herbívoro das florestas neotropicais
Keywords: Atlantic forest; Extinction risk; Habitat patchiness; Occupancy models; Scale of effect; Tapirus